2017
DOI: 10.1111/jopy.12351
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual differences in the intraindividual association of competence and well‐being: Combining experimental and intensive longitudinal designs

Abstract: Results show that interindividual differences in the association of competence fulfillment and well-being are a matter of degree, but not quality. They also support the claim that need satisfaction and dissatisfaction are more than psychometric opposites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
2
31
0
Order By: Relevance
“…One aim of these studies was the analysis of the affective consequences of negative performance feedback. Results concerning these dependent variables are reported in Neubauer et al (2017). The present paper focuses on the analysis of behavioral consequences (i.e., performance measures) of negative performance feedback.…”
Section: Methods Participantsmentioning
confidence: 99%
“…One aim of these studies was the analysis of the affective consequences of negative performance feedback. Results concerning these dependent variables are reported in Neubauer et al (2017). The present paper focuses on the analysis of behavioral consequences (i.e., performance measures) of negative performance feedback.…”
Section: Methods Participantsmentioning
confidence: 99%
“…Notably, inter-individual differences in the effect of need fulfillment on affective outcomes are a controversial issue in SDT: given its universality claim, need fulfillment should have positive outcomes for all individuals. However, inter-individual differences in these positive effects might be rather a matter of quantity than quality, meaning that the effects of need satisfaction (frustration) should be positive (negative) for virtually all individuals, but to different degrees (Neubauer, Lerche, & Voss, 2018;Ryan, Soenens, & Vansteenkiste, 2019). This reasoning is in line with the size of the random effects we obtained in the present work: In all cases, the standard deviations of the random effects (= the square roots of the random variances reported in Table 4) were around the same size as the absolute values of the corresponding fixed effects.…”
Section: Inter-individual Differences: Satiation and Sensitization?mentioning
confidence: 99%
“…Findings showed that inter-individual differences in the withinperson association of daily need fulfillment and positive affect were associated with, for example, the child's extraversion (stronger association in mothers with less extraverted children). Neubauer, Lerche, and Voss (2018) examined the predictive validity of interindividual differences in the within-person association between need fulfillment and wellbeing. Findings from this study showed that participants differed in the degree to which daily satisfaction (frustration) of the needs for autonomy, competence, and relatedness was associated with better (worse) current mood.…”
Section: The Benefits Of a Within-person Perspectivementioning
confidence: 99%